2010
DOI: 10.2478/s12175-010-0022-x
|View full text |Cite
|
Sign up to set email alerts
|

Coloring of lattices

Abstract: ABSTRACT. The concept of coloring is studied for graphs derived from lattices with 0. It is shown that, if such a graph is derived from an atomic or distributive lattice, then the chromatic number equals the clique number. If this number is finite, then in the case of a distributive lattice, it is determined by the number of minimal prime ideals in the lattice. An estimate for the number of edges in such a graph of a finite lattice is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…Thus a similar question can be asked for commutative semigroups with 0, see [9]. In a recent paper [10] Nimbhokar, Wasadikar and Demeyer have shown that Beck's conjecture holds for the class of ∧-semilattices with 0, i.e., commutative and idempotent semigroups with 0, see [4] and [7].…”
mentioning
confidence: 93%
“…Thus a similar question can be asked for commutative semigroups with 0, see [9]. In a recent paper [10] Nimbhokar, Wasadikar and Demeyer have shown that Beck's conjecture holds for the class of ∧-semilattices with 0, i.e., commutative and idempotent semigroups with 0, see [4] and [7].…”
mentioning
confidence: 93%
“…Nimbhorkar, Wasadikar and Pawar in [9] have associated a graph with a lattice L with 0 by saying that two elements are adjacent if and only if their meet is 0. Similarly we can define a graph with a lattice L with 0 by saying that two nonzero elements a, b ∈ L are adjacent if and only if a ∧ b = 0 and call this graph as the zero divisor graph of L and denote it by Γ (L).…”
Section: Definition 2 a Connected Acyclic Graph Is Called A Treementioning
confidence: 99%
“…The papers of Gadenova [5], Bollobas and Rival [1] discuss the properties of covering graphs derived from lattices. In [9] Nimbhorkar, Wasadikar and Pawar defined graphs on a lattice L with 0, by defining adjacency of two elements x, y ∈ L by x ∧ y = 0.…”
Section: Introductionmentioning
confidence: 99%
“…Nimbhorkar, Wasadikar and Pawar [10] associated a zero-divisor graph to a lattice L with 0, whose vertices are the elements of L and two distinct elements are adjacent if and only if their meet is 0. Similarly in [11] we define a graph of a lattice L with 0.…”
Section: Some Realizable and Non Realizable Graphsmentioning
confidence: 99%
“…The papers of Gadenova [6], Bollobas and Rival [2] discuss the properties of covering graphs derived from lattices. Nimbhorkar, Wasadikar and Pawar [10] defined the zero-divisor graphs of a lattice L with 0, by defining the adjacency of two elements x, y ∈ L by x ∧ y = 0.…”
Section: Introductionmentioning
confidence: 99%